Role of new vaccinators/pharmacists in life-course vaccination - T. Mark Doherty; Lois Privor-Dumm (Annals of Medicine, 2024)
Background Vaccines against diseases such as herpes zoster, pneumococcus and influenza are broadly recommended for older adults, but uptake is frequently low.Vaccination Bottleneck Part of the reason may be that access to adult vaccination can be problematic, particularly for minorities and other under-served populations. Potential barriers include complex procedures, limited resources in healthcare systems and lack of structured infrastructure.Stress-testing expended vaccination The Covid-19 pandemic necessitated rapid expansion of the infrastructure to deliver adult vaccination, and triggered the use of facilities including pharmacies, schools, faith-based organizations, community organizations, shops and hair salons, drive-through centres and mobile vaccination units.Improved adult vaccination system Although many such initiatives were temporary, they demonstrated the principle of effective expansion of adult vaccination and education to a range of new providers and settings. Of these, pharmacist involvement in immunization in particular has consistently been shown to be associated with increased immunization rates.Integration of new vaccinators This review discusses results from attempts to expand and simplify the adult vaccination process, potentially allowing vaccination to be initiated by the recipient and completed in a single visit. These studies suggest that expanding adult vaccination access to new providers and/or new settings will require development of an integrated plan for preventive healthcare, covering areas such as setting target coverage rates, financial support, and development of immunization information systems accessible to all vaccination providers to maintain accurate immunization records and support interventions such as reminders.